Analysis of the Amino Acid Requirement for a Normal αIIbβ3 Maturation at αIIbGlu324 Commonly Mutated in Glanzmann Thrombasthenia - Milet-Marsal, Sandrine; Breillat, Christelle; Peyruchaud, Olivier; Nurden, Paquita; Combrié, Robert; Nurden, Alan T.; Bourre, François (Thrombosis and Haemostasis, 2002)
Glanzmann thrombasthenia is an inherited bleeding disorder arising from quantitative or qualitative defects of the αIIbβ3 integrin of platelets. Here, we report that PCR-SSCP analysis and DNA sequencing revealed a homozygous single base pair substitution in exon 12 of the αIIb gene leading to a Glu324 (E) to Lys (K) substitution in the αIIb subunit in a patient with Type I disease. As this mutation is found on at least 3 continents, the codon for Glu324 may be a mutational hotspot of the disease. To better understand this mutation, we analyzed the effect of substituting E324 with A324, L324, D324, Q324, N324, S324, as well as K324, looking at both αIIbβ3 maturation and cell surface expression in transiently transfected Cos-7 cells. The maturation state of the receptor clearly correlated with the level of cell membrane expression. Maturation efficiency was dependent on the electric charge as well as the size of the side chain of the amino acid present in what is a highly conserved N-terminal position in the third β-strand of blade 5 of the αIIbβ-propeller.
Keywords: Glanzmann thrombasthenia; αIIbβ3 integrin; αIIb mutation; sitedirected mutagenesis; maturation defect